2014
DOI: 10.1001/jamaneurol.2013.5699
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Relapse and Treatment Failure Rates Among Patients With Neuromyelitis Optica

Abstract: euromyelitis optica (NMO) is an inflammatory demyelinating disease of the central nervous system (CNS) distinct from multiple sclerosis (MS). It is characterized by optic neuritis (ON), longitudinally extensive transverse myelitis (TM), and, in approximately 70% of cases, the presence in serum of IgG antibodies that target aquaporin 4 (AQP4-IgG; also known as NMO-IgG). Patients with neuromyelitis optica spectrum disorder (NMOSD) are seropositive for AQP4-IgG and have evidence of an inflammatory event consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
236
0
8

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 263 publications
(261 citation statements)
references
References 15 publications
9
236
0
8
Order By: Relevance
“…Another retrospective study of 103 patients with AQP4-IgG-positive NMOSD confirmed these findings, revealed a reduction of the median ARR in 89 % of patients (median of 1.5 pretreatment to 0 on AZA), and an improvement or stabilization of the EDSS in 78 % of patients, but again had a high discontinuation rate of AZA (46 %) [78]. A third retrospective study of 31 patients with AQP4-IgG-positive or AQP4-IgG-negative NMOSD described a reduction in the mean ARR from 2.26 to 0.63 with a failure rate in 53 % of patients, despite concomitant prednisone therapy [79]. Another retrospective study of AZA plus long-term low-dose corticosteroid therapy in 77 Chinese patients found a relapse-free status at median follow-up of 19 months in 44 patients (57.1 %) and significant improvements of the ARR, EDSS, and modified Rankin Scale [80].…”
Section: Azamentioning
confidence: 99%
See 4 more Smart Citations
“…Another retrospective study of 103 patients with AQP4-IgG-positive NMOSD confirmed these findings, revealed a reduction of the median ARR in 89 % of patients (median of 1.5 pretreatment to 0 on AZA), and an improvement or stabilization of the EDSS in 78 % of patients, but again had a high discontinuation rate of AZA (46 %) [78]. A third retrospective study of 31 patients with AQP4-IgG-positive or AQP4-IgG-negative NMOSD described a reduction in the mean ARR from 2.26 to 0.63 with a failure rate in 53 % of patients, despite concomitant prednisone therapy [79]. Another retrospective study of AZA plus long-term low-dose corticosteroid therapy in 77 Chinese patients found a relapse-free status at median follow-up of 19 months in 44 patients (57.1 %) and significant improvements of the ARR, EDSS, and modified Rankin Scale [80].…”
Section: Azamentioning
confidence: 99%
“…MMF treatment for a median of 20-27 months resulted in a reduction of the ARR by 80-93 % and improvement of the median EDSS in 3/ 4 studies (not reported in 1). More than 90 % of patients had stable or improved disability [83,84], and 46-65 % were relapse-free [79,81,83,84]. Discontinuation rates due to disease activity or side effects were 15-25 %.…”
Section: Mycophenolate Mofetilmentioning
confidence: 99%
See 3 more Smart Citations